2019
DOI: 10.2147/itt.s212760
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Factors Associated With Adherence To Immunosuppressive Therapy And Barriers In Asian Kidney Transplant Recipients</p>

Abstract: BackgroundMedication non-adherence is the major risk factor for rejection episodes. The aim of this study was to determine the risk factors associated with adherence to immunosuppressive regimen and its barriers among kidney transplant (KT) recipients.MethodsA cross-sectional study was performed in two outpatient post-transplant clinics in Mashhad, northeast of Iran. All patients who attended the clinics from August to October 2017 were included. Patients’s knowledge, adherence to immunosuppressive regimen, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 30 publications
0
12
0
5
Order By: Relevance
“…Although a Brazilian study reported that higher family income was the only factor that was associated with immunosuppressive nonadherence because of lower income recipients benefiting from better access to care and coverage of health-care costs after transplantation ( Marsicano et al, 2015 ), higher family income could support transplant recipients to pay for their IM, check the IM concentration, and improve the quality of life in China. Also, the life quality manifested a direct effect on medication adherence in Asian RTPs ( Ganjali et al, 2019 ). In addition, religion issues also displayed a considerable influence on positive attitudes toward transplantation ( Messina, 2015 ; Kobus et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although a Brazilian study reported that higher family income was the only factor that was associated with immunosuppressive nonadherence because of lower income recipients benefiting from better access to care and coverage of health-care costs after transplantation ( Marsicano et al, 2015 ), higher family income could support transplant recipients to pay for their IM, check the IM concentration, and improve the quality of life in China. Also, the life quality manifested a direct effect on medication adherence in Asian RTPs ( Ganjali et al, 2019 ). In addition, religion issues also displayed a considerable influence on positive attitudes toward transplantation ( Messina, 2015 ; Kobus et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most common pattern of IM non-adherence in our study remained the timing adherence (30.1%). In fact, another study reported that up to 86.7% of KTR could have problems in timing adherence [17] . As forgetfulness is one of the main reasons of medication non-adherence [18] , reducing the number of daily doses such as once daily drug regimen may be able to improve medication adherence [ 16 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pacientų išgyvenamumas po inksto transplantacijos pastaruoju metu padidėjo dėl chirurginės technikos patobulėjimo ir efektyvių imunosupresinių vaistų skyrimo, tačiau tinkamas šių vaistų vartojimas išlieka dideliu iššūkiu [1]. Nustatyta, kad imunosupresinių vaistų vartojimo režimo nesilaikymas po inksto transplantacijos gali būti būdingas daugiau negu 50 proc.…”
Section: įVadasunclassified
“…Netinkamas imuninę sistemą slopinančių vaistų vartojimas padidina inksto transplantato atmetimo epizodų riziką net 7 kartus [3]. Ši problema paveikia pacientų bei transplantatų išgyvenamumą ir ženkliai padidina gydymo išlaidas [1]. Nors netinkamo imunosupresinių vaistų vartojimo rizikos veiksniai varijuoja tarp bendruomenių, tačiau jų identifikavimas gali padėti kurti strategijas, kaip pašalinti, kontroliuoti šiuos veiksnius, padidinti šių vaistų vartojimą, sumažinti išlaidas [1] ir tokiu būdu pagerinti paciento bei inksto transplantato išgyvenamumą [4].…”
Section: įVadasunclassified
See 1 more Smart Citation